Pelatihan Keterampilan Bahasa Mandarin Bagi KaryawanPelaksana dan Karyawan Pimpinan Di PTP. Nusantara IV Persero Sumatera Utara - Sheyra Silvia Siregar; Eka Nurnella Manihuruk (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This service activity is entitled Mandarin Skills Training for Implementing Employees and Leadership Employees at PTP. Nusantara IV Persero North Sumatra. This service will be carried out in the form of debriefing training activities in the form of basic Mandarin language skills and Mandarin in the field of agriculture. The purpose of carrying out this service activity is as a debriefing for implementing employees and leadership employees considering the rapid development of investors from China, especially in the agricultural sector in Indonesia. This is in accordance with the development of the industrial world which has reached the stage of the industrial revolution 5.0. This training is considered important because it is expected to be a medium in an effort to improve the quality of human resources (HR) working in PTP. Nusantara IV Persero North Sumatra. Another purpose is to provide an introduction to Chinese cultural values that are considered necessary for employees to know so that they are expected to assist in efforts to improve the quality of performance and establish good communication between investors and the Business Entity which in this case is PTP. Nusantara IV Persero North Sumatra. The method used is distance learning method (synchronization method and asynchronous method). After participating in this training, it is hoped that it will help improve the quality of work by implementing employees and leadership employees who are built through Mandarin language skills and knowledge of Chinese culture as a medium of communication at work. Based on the activities that have been carried out, it was found that 93% of the training participants were able to master basic Mandarin. These results were obtained through an assessment process in the form of pre-test and post-test so that it can be concluded that this service activity is able to improve human resources in PTP. Nusantara IV Persero North Sumatra.